2020
DOI: 10.1038/s41598-020-64856-x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of optimal fertigation implications in different soils on reducing environmental impacts of agricultural nitrate leaching

Abstract: Excessive and incorrect use of nitrogen (N) fertilizers in agriculture leads to high nitrate leaching to groundwater and harmful effects on the environment. The main objective of this research was to optimize the N fertigation scheduling for a surface micro-irrigation system in different soils. N uptake by corn and its losses were investigated for two fertigation scheduling scenarios including regional recommendation scheduling with three fertigation events and a weekly application schedule. The fertigation sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Recent advances in precision fertilizer systems may increase fertilizer use-efficiency, while reducing the risk of salinization and contamination of both underground and surface waterbodies. Specifically, fertigation technologies, in which dissolved fertilizers are distributed through drip irrigation systems, were shown to optimize fertilizer use-efficiency and reduce agriculture's environmental footprint (Azad et al, 2020).…”
Section: Fertilizing and Manuring Schemesmentioning
confidence: 99%
“…Recent advances in precision fertilizer systems may increase fertilizer use-efficiency, while reducing the risk of salinization and contamination of both underground and surface waterbodies. Specifically, fertigation technologies, in which dissolved fertilizers are distributed through drip irrigation systems, were shown to optimize fertilizer use-efficiency and reduce agriculture's environmental footprint (Azad et al, 2020).…”
Section: Fertilizing and Manuring Schemesmentioning
confidence: 99%
“…In addition, optimizing the amount of N fertilizer for different soil textures can effectively reduce nitrate leaching. Azad et al (2020) reported that the amount of nitrate leaching in sandy soil decreased from 122.18 to 44.98 kg ha −1 , and loam and clay decreased from 22.1 to 13.9 kg ha −1 by optimized fertilization [ 47 ]. Reducing the N fertilizer rate can significantly reduce nitrate leaching.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of elevated nitrate concentrations (GW NO 3 ) in groundwater is a persistent concern in numerous countries around the globe, especially in shallow aquifers beneath highly agrarian areas and soils offering higher permeability . Elevated nitrate above the permissible limit of 45 mg/L is a major groundwater problem in agrarian South Asia as well as in India. Although different natural and human practices like deposition from the atmosphere, , crop nitrogen fixation, use of animal manure, sewage application in agriculture, , and faulty urban sewages , are argued to contribute to nitrate concentrations, the excess use of chemical fertilizers is perceived as the primary source of high GW NO 3 . , Studies were conducted to limit nitrate leaching from the source by controlling fertilizer applications, tracking nitrate movement pathways, and developing treatment strategies including biological methods. Despite these studies, encounters with high concentrations of GW NO 3 in the global aquifers are still a persistent concern to policymakers …”
Section: Introductionmentioning
confidence: 99%